Strategi Manajemen Kurikulum Dalam Peningkatan Kualitas Pendidikan: Studi kasus di MTS Nurul Islam Desa Alai - Hoirotul Hasanah; Siti Fatimah; Nadhea Pratiwi; Maisin Dila Saputri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Curriculum management is a regulatory activity that includes planning, organizing, implementing and supervising or evaluating so that educational programs can run well and in sync with predetermined goals. From the background above, the author formulates the title